Validation of sport education as a reference curriculum model in higher education supporting the MBKM curriculum - Ramadhan, Riki; Effendy, Fauzan; Mudzakir, Dicky Oktora (Journal Sport Area, 2024)
Background Problems: In Indonesia, sports study programmes must adapt to the Merdeka Belajar Kampus Merdeka (MBKM) curriculum, which is based on outcome-based education (OBE). In OBE, Learning Outcomes of Graduates (LOG) are carried out through the implementation of learning, or outcome-based learning and teaching (OBLT), using a pedagogical model that is in accordance with the development of the MBKM curriculum, and the pedagogical model associated with the OBE-based MKBM curriculum is Sport Education (SE). SE is a pedagogical model that is consistent with OBE principles and is considered relevant for implementing the MBKM curriculum. However, there is no empirical evidence to support the reliability of SE as a curriculum model in sport study programmes at the higher education (HE) level, hence the need for a validation study. Research Objectives: This study aims to validate and empirically test the reliability of SE as a curriculum model for sports study programmes at the higher education level. Methods: This study used the 4-D R&D methodology, which involved small-scale (56 students) and large-scale (147 students) trials. Reliability was assessed using the intraclass correlation coefficient with SPSS. Findings and Results: Results suggest that SE works well with OBE principles within the MBKM framework, providing sports studies programmes with a powerful way to teach new things that are useful in the real world. Further research is recommended to validate SE in sport-specific contexts such as martial arts. Conclusion: The study concluded that SE is a reliable reference curriculum model for sport studies programmes at the HE level, which is aligned with OBE principles as required by the MBKM curriculum. The findings advocate wider adoption of SE in HE learning, particularly for sport studies programmes, subject to further validation in a range of sport disciplines using SE.